2022
DOI: 10.3390/ijms23179792
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Black Box of Intra-Amniotic Infection and Its Impact on the Premature Lung: From Clinical and Preclinical Perspectives

Abstract: Intra-amniotic infection (IAI) is one major driver for preterm birth and has been demonstrated by clinical studies to exert both beneficial and injurious effects on the premature lung, possibly due to heterogeneity in the microbial type, timing, and severity of IAI. Due to the inaccessibility of the intra-amniotic cavity during pregnancies, preclinical animal models investigating pulmonary consequences of IAI are indispensable to elucidate the pathogenesis of bronchopulmonary dysplasia (BPD). It is postulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 146 publications
0
6
0
Order By: Relevance
“…Whether or not the amniotic cavity is a sterile environment is a hotly debated topic in the current literature; however, several studies have demonstrated a variety of organisms live within the amniotic fluid, ranging from Gram-positive and negative bacteria, viruses, and fungi to genital mycoplasma species, such as Ureaplasma. 36,[38][39][40][41][42] Several inflammatory mediators have been implicated in the prenatal pathogenesis of BPD, including interleukin (IL)-1α, IL-1β, IL-6, IL-8, and tumor necrosis factor (TNF)-α. 37,43 These proinflammatory cytokines have been shown to alter both structure and function of lung tissue in several animal trials.…”
Section: Pulmonary Inflammationmentioning
confidence: 99%
See 3 more Smart Citations
“…Whether or not the amniotic cavity is a sterile environment is a hotly debated topic in the current literature; however, several studies have demonstrated a variety of organisms live within the amniotic fluid, ranging from Gram-positive and negative bacteria, viruses, and fungi to genital mycoplasma species, such as Ureaplasma. 36,[38][39][40][41][42] Several inflammatory mediators have been implicated in the prenatal pathogenesis of BPD, including interleukin (IL)-1α, IL-1β, IL-6, IL-8, and tumor necrosis factor (TNF)-α. 37,43 These proinflammatory cytokines have been shown to alter both structure and function of lung tissue in several animal trials.…”
Section: Pulmonary Inflammationmentioning
confidence: 99%
“…The term “chorioamnionitis” is commonly used to describe a variety of inflammatory disorders and antenatal infections with a spectrum of severity 35 . Associated clinical findings include some combination of maternal fever, maternal or fetal tachycardia, maternal leukocytosis, uterine tenderness, or purulent vaginal discharge; however, these findings correlate poorly with diagnosis of true intraamniotic infection 35,36 . As a result, the National Institute of Child Health and Development proposed the term “intrauterine inflammation, infection, or both” (abbreviated as “Triple I”) as a replacement for “chorioamnionitis” in 2016 35 …”
Section: Pathogenesis Of Bpdmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, bacterial colonization of the upper airways with Enterococcu s Enterobacter Staphylococcus and Escherichia species was identified to be associated with BPD [ 8 ]. But the impact of microbiota on the immature lung and the risk for BPD remains controversial [ 9 ]. The two largest meta-analyses on this topic found an association between chorioamnionitis or the pulmonary colonization with bacteria of the genus Ureaplasma and BPD, but both reports point to the uncertainty due to potential biases in the published data despite the statistically significant impact on BPD [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%